# Simplifying expressions

Simplify the following expressions:

a. 3x-2/2x2+x-3 Divide by 9x-6/2x-2

b.(108)1/2- (48)1/2+ (192)1/2 (should be exponent 1/2)

c. (20x3+3x2-4x+5)/(4x2+3x-7) (should be exponent 3 and 2,2).

Â© BrainMass Inc. brainmass.com February 4, 2021, 6:33 pm ad1c9bdddfhttps://brainmass.com/math/basic-algebra/simplifying-expression-function-15152

#### Solution Preview

a.)

[(3x-2)/(2x^2+x-3)]/[(9x-6)/(2x-2)]

=[(3x-2)*(2x-2)]/[(9x-6)(2x^2+x-3)]

=[(3x-2)*2*(x-1)]/[3*(3x-2)*(2x^2+3x-2x-3)]

=[2*(x-1)]/[3*(2x^2+3x-2x-3)]

=[2*(x-1)]/[3*(2x+3)*(x-1)]

=2/[3*(2x+3)] --Answer

b.)

(108)^(1/2)- (48)^(1/2)+ ...

#### Solution Summary

This shows how to simplify polynomial expressions.

$2.19